2021
DOI: 10.1371/journal.pone.0255138
|View full text |Cite|
|
Sign up to set email alerts
|

A cross-sectional survey of hard ticks and molecular characterization of Rhipicephalus microplus parasitizing domestic animals of Khyber Pakhtunkhwa, Pakistan

Abstract: Background In tropical and subtropical countries, tick infestation causes major public health problems and considerable financial losses to the livestock industry. This study was aimed to assess the species composition of richness and analyze the phylogeny of Rhipicephalus microplus in the District Bannu of Khyber Pakhtunkhwa, Pakistan. Methods Collected ticks were identified morphologically and DNA extracted from R. microplus was amplified and subjected to sequencing. Results A total of 3,600 animals were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In Pakistan, the environmental conditions are conducive to tick reproduction and development. Although, several studies have identified ticks from diverse hosts across different geographical locations in Pakistan [ 23 , 25 , 26 , 36 , 37 , 38 , 39 ]. Only one study had cataloged the tick species morpho-taxonomically infesting dogs thus far, from the Baluchistan province of Pakistan [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Pakistan, the environmental conditions are conducive to tick reproduction and development. Although, several studies have identified ticks from diverse hosts across different geographical locations in Pakistan [ 23 , 25 , 26 , 36 , 37 , 38 , 39 ]. Only one study had cataloged the tick species morpho-taxonomically infesting dogs thus far, from the Baluchistan province of Pakistan [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the overall prevalence of tick infestation was 61% in dogs, while across different districts, a higher prevalence of ticks was observed in district Mardan (14.7%) followed by Peshawar (13%), Swabi (12%), Charsadda (11%), and Malakand (10.3%). In the last three decades, several studies have attempted to report the prevalence rates of tick infestation, ranging from 6.9% to 86.5% in livestock across different geographical localities of the country [ 16 , 23 , 25 , 26 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Our results also fall within the same range and support these reports.…”
Section: Discussionmentioning
confidence: 99%
“…Pakistan is home to several infectious zoonoses [ 8 , 9 ], vector-borne diseases [ 10 , 11 ], and vectors [ 12 ]. However, cutaneous leishmaniasis greatly affected the people of Pakistan, specifically those of Khyber Pakhtunkhwa province, and several studies reported the disease in southern Khyber Pakhtunkhwa [ 13 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Standard procedures and bio-safety measures were followed during collection of tick sample from animals (Walker et al, 2003;Rooman et al, 2021). Ticks were collected randomly from cattle population of farms, gaushalas and panjrapoles located under the area of the study during the months of April, 2017 to March, 2018 (Table 1).…”
Section: Collection Of Tickmentioning
confidence: 99%